RISIKO OSTEOPOROSIS DI INDONESIA - Jahari, Abas Basuni; Prihatini, Sri (PERSATUAN AHLI GIZI INDONESIA, 2007)
RISK OF OSTEOPOROSIS IN INDONESIABackground: Osteoporosis is on of growing problems in the world which is related to ageingprocess. It is estimated that in the year 2050 around 50% bone fracture in Asia is associated withosteoporosis. However, epidemiological information about osteoporosis in Indonesia is still rarelyavailable.Objective: To provide information on the magnitude of osteoporosis in Indonesia.Method: In 1999 and 2003-2005 PT FBI carried free Bone Mineral Density (BMD) examination inseveral provinces of Indonesia. The total samples of 126,265 subjects were those who came tothe examination center set by the PT FBI. The equipment used to examine BMD is ”SaharaClinical Bone Sonometer”.Results: It is found that the proportion of risk of osteoporosis was 19.7 percent in 2002, 7.7percent in 2003, 7.0 percent in 2004 and 10.7persen in 2005. The pattern of the problem wassimilar from 2002 to 2005; the risk of osteoporosis is increasing following the ages. The proportionof osteophenia was higher than that of risk of osteoporosis. The proportion of osteophenia was36.0 percent in 2002, 46.8 percent in 2003, 46.5 percent in 2004 and 41.8 percent in 2005. Theproportion of risk of osteoporosis below 55 years of age was less in male than in female, howeverin the age of >= 55 years the proportion was higher in female than in male subjects.Conclusion: The proportion of risk of osteoporosis was less in 2005 than that in 2002. However,this figure is not an indication of decreasing problem of risk of osteoporosis, because the nature ofthe population distribution and sampling method did not provide evidence of representativenessfor the areas. The problem of ostephenia relatively did not change much from 36.0 percent in 2002to 41.8 percent in 2005 or around 40 percent. This means that four out of 10 elderly having risk ofdeveloping osteoporosis.Recommendation: Problem of osteoporosis should be taken care not only for older people butshould start from the younger age. To obtain more representative figures on osteoporosis a moreappropriate designed study needs to be carried out.Keywords: osteoporosis, osteophenia, bone mineral density